Re-evaluation of the Mandevilla subsessilis species complex and resurrection of M. platydactyla (Apocynaceae: Apocynoideae) - Pérez, Lucio Lozada; Cárdenas, Leonardo O. Alvarado (Phytotaxa, 2015)
The present work re-evaluates the Mandevilla subsessilis complex (Apocynaceae: Apocynoideae). Based on morphological analysis, including UPGMA, we recognize two separate species, respectively distributed primarily west and east of the Isthmus of Tehuantepec: M. platydactyla (with M. mollis as a synonym) and M. subsessilis.  Mandevilla platydactyla is found from the Sierras de Chiapas to Nicaragua, whereas M. subsessilis is endemic to Mexico, particularly the Sierra Madre del Sur.